The impact of mixed planting of Poaceae species in the Qinghai-Tibet plateau region on forage yield, soil nutrients, and soil microbial communities - Li, Sida; Xiang, Xuemei; Shi, Zhenghai; Liu, Wen-hui; Liang, Guoling; Zhang, Yongchao; Li, Wen (Frontiers in Plant Science, 2024)
Establishing cultivated grassland in the Qinghai-Tibet Plateau region is an effective method to address the conflict between vegetation and livestock. However, the high altitude, low temperature, and arid climate in the region result in slow regeneration and susceptibility to degradation of mixed cultivation grassland containing perennial legumes and gramineous plants. Therefore, we aim to through field experiments, explore the feasibility of establishing mixed cultivation grassland of Poaceae species in the region by utilizing two grass species, Poa pratensis L. and Puccinellia tenuiflora. By employing a mixture of P. pratensis and P. tenuiflora to establish cultivated grassland, we observed significant changes in forage yield over time. Specifically, during the 3rd to 6th years of cultivation, the yield in the mixed grassland was higher than in monocultures. It exceeded the yield of monoculture P. tenuiflora by 19.38% to 29.14% and surpassed the monoculture of P. pratensis by 17.18% to 62.98%. Through the analysis of soil physicochemical properties and soil microbial communities in the cultivated grassland, the study suggests that the mixed grassland with Poaceae species can enhance soil enzyme activity and improve soil microbial communities. Consequently, this leads to increased soil nutrient levels, enhanced nitrogen fixation efficiency, and improved organic phosphorus conversion efficiency. Therefore, establishing mixed grasslands with Poaceae species in the Qinghai-Tibet Plateau region is deemed feasible.